2016
DOI: 10.1371/journal.pone.0158992
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence as a Predictor of Death: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe association between urinary incontinence (UI) and increased mortality remains controversial. The objective of our study was to evaluate if this association exists.MethodsWe performed a systematic review and meta-analysis of observational studies comparing death rates among patients suffering from UI to those without incontinence. We searched in Medline, Embase and the Cochrane library using specific keywords. Studies exploring the post-stroke period were excluded. Hazard ratios (HR) were pooled u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 68 publications
3
47
0
3
Order By: Relevance
“…The factors of adjustment were chosen from previous publications or when they were associated with mortality in univariate analyses. [5,6] Continuous variable were introduced as categorical or dichotomous variable when not linear in the Cox model. Furthermore, the proportion of UI, the proportion of IUC, and one-year mortality decreased over the study period (Table e-1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors of adjustment were chosen from previous publications or when they were associated with mortality in univariate analyses. [5,6] Continuous variable were introduced as categorical or dichotomous variable when not linear in the Cox model. Furthermore, the proportion of UI, the proportion of IUC, and one-year mortality decreased over the study period (Table e-1).…”
Section: Discussionmentioning
confidence: 99%
“…The respective figure for IUC was 729 deaths among patients with IUC (62.3%) compared to 470 among patients without IUC (18.2%, p <0.001). UI and IUC were both associated with death in unadjusted survival analysis: hazard ratio (HR) 6 Mortality in continent and incontinent patients was higher among those receiving an IUC (Figure 1). Compared to patients without UI or IUC, patients with IUC (HR 3.42; 95% CI 2.35-4.97), patients with UI but no IUC (HR 4.70; 95% CI 3.88-5.70), and patients with UI and IUC (HR 10.24; 95% CI 8.72-12.03) were at higher risk of death.…”
Section: Association Between Urinary Incontinence Indwelling Cathetementioning
confidence: 99%
See 1 more Smart Citation
“…Urinary incontinence (UI) occurs in up to one-third of adult women, with urgency type UI (UUI), specifically, increasing greatly with age [1][2][3][4][5][6][7]. UI may also be associated with increased mortality even after adjusting for chronic conditions [8]. Treatment options for UI include nonpharmacological and pharmacological interventions that rarely ameliorate all symptoms [9].…”
Section: Introductionmentioning
confidence: 99%
“…) and is a predictor of higher mortality, especially among older people (John et al 2016). The study reported here aims to explore help-seeking behaviour in older people with UI.…”
mentioning
confidence: 99%